CARLA MALDONADO, FINN BORCHSENIUS & CHARLOTTE M. TAYLOR - Maldonado, Carla; Borchsenius, Finn; Taylor, Charlotte M. (Phytotaxa, 2014)
The new species Elaeagia coriacea (Condamineeae, Rubiaceae), from southern Ecuador, is here described and illustrated. It differs from Elaeagia ecuadorensis in its abaxially papillate leaves and by the short obtuse calyx lobes.